2018
DOI: 10.5539/jfr.v7n2p86
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Dietary Exposure to Pesticide Residues and Its Association with Pesticide Application Practices among Vegetable Farmers in Arusha, Tanzania

Abstract: This study was conducted to assess dietary exposure to pesticide residues and pesticide application practices leading to the presence of these residues among vegetable farmers in Arusha, Tanzania. Face-to-face interviews using semi-structured questionnaires (including 24-hour recall and food frequency questionnaire techniques) were conducted to collect information on pesticide application practices and vegetable consumption, from 76 farmers. A sample of ready-to-eat vegetables was collected from each farmer's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 35 publications
0
21
2
Order By: Relevance
“…Given a provision of 3 years from 2011 implies that, endosulfan should have been stopped from the use by 2014. However, a survey done in Arusha district in 2015 revealed that farmers were still applying this pesticide in vegetables (Kiwango et al, ), indicating a need for improved reinforcement of pesticide use management regulations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given a provision of 3 years from 2011 implies that, endosulfan should have been stopped from the use by 2014. However, a survey done in Arusha district in 2015 revealed that farmers were still applying this pesticide in vegetables (Kiwango et al, ), indicating a need for improved reinforcement of pesticide use management regulations.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that farmers did not observe the preharvest interval after pesticide application. Kiwango et al () and Mhauka () report that most of the vegetable farmers do not adhere to the preharvest interval. Quantifying pesticide residues in vegetables at levels above MRL implies that the consumers are exposed to levels of health concern.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations